Integrating Islamic Values into a Science Comic Book as an Instructional Media - Tamam, Badrud; Sutarja, Maria Chandra; Rakhmawan, Aditya; Mus'if, Ach. (Jurnal Penelitian dan Pembelajaran IPA, 2023)
This study examined the validity of a science comic book integrated with Islamic values. The development of the book followed the steps of ADDIE (Analyze, Design, Develop, Implement, and Evaluate). The product was validated by an expert in Islamic studies, an expert in instructional media, an expert in instructional material, and a science teacher. A questionnaire was used to obtain data validation results. The expert validation results showed a score of 3.8 for the integrated Islamic values, 3.5 for the material, 3.5 for the book function as instructional media, and 3.7 for the product practicality, with all scores falling into the "very valid" category. At the implementation stage, the book was tried on a student individual, a small group of students, and a larger group of students to conduct practicality of the product from students’ responses. The students’ responses showed scores of 86.25% (individual trials), 84.44% (small-group trials), and 85.94% (large-group trials), with all scores falling into the very good category. These results indicate that the science comic book integrated with Islamic values can be implemented in the science classroom. At the evaluation stage, formative evaluation was conducted. It collects expert suggestions to revise a comic